Flexibility is associated with motor competence in schoolchildren - Lopes, Luís (2017)
Available data on the associations between motor competence (MC) and flexibility are limited and result inconclusive. This study aims to examine the relationship between flexibility and MC in children. The sample comprised 596 Portuguese children (47.1% girls) aged 9.7± 0.6 years. Motor competence was evaluated with the body coordination test, Korperkoordination Test fur Kinder. Cardiorespiratory fitness (20-m shuttle run), muscular strength (curl-up and push-up tests), and flexibility (back-saver sit and reach and trunk-lift tests) were evaluated using the Fitnessgram Test Battery. Z-scores by age and gender for the physical fitness tests were constructed. Analysis of variance and regression analysis were performed. Participants in the healthy zone groups of both flexibility tests exhibited significantly better scores of MC than the participants under the healthy zone (P < 0.001). Back-saver sit and reach and trunk-lift Z-scores, either individually or as a sum, were significant predictors of MC (P < 0.05 for all) after adjustments for the other physical fitness components, age, body mass index, and socioeconomic status, in both genders. Our findings highlight the importance of promoting and developing flexibility, as well as the other health-related physical fitness components in schoolchildren to reach adequate levels of MC